A 3D hierarchical magnetic Fe@Pt/Ti(OH)4 nanoarchitecture for sinter-resistant catalyst1. Issue 80 (2nd September 2015) - Zhang, Chao; Zhou, Yuming; Zhang, Yiwei; Zhang, Zewu; Xu, Yuanmei; Wang, Qianli
<x xml:space="preserve">Abstract</x> The synthesized 3D hierarchical magnetic Fe@Pt/Ti(OH)4 nanoarchitecture shows an excellent anti-sintering property for the physical barrier effects of Ti(OH)4 nanorods and a well recyclability.